Z zdravili povzročena poškodba pljučnega intersticija - Morgan, Tina (Farmacevtski vestnik, 2025)
Drug-induced interstitial lung injury is a rare but important cause of interstitial lung disease and accounts for 3–5% of cases. Over 400 drugs – including antirheumatics, antineoplastics, and antiarrhythmics – have been associated with this condition. The clinical presentation ranges from asymptomatic disease to life-threatening respiratory failure. Early stages are potentially reversible with medicine discontinuation and anti-inflammatory therapy, but delayed recognition can lead to irreversible and potentially progressive fibrosis. Risk factors include older age, smoking, previous interstitial lung disease, and chest radiotherapy. Diagnosis is complex and is based on the exclusion of other causes, in particular infection and pulmonary disease. Management is based on discontinuation of the suspect causative agent and in more severe cases, on the prolonged use of systemic glucocorticosteroids. Immune checkpoint inhibitors have emerged as agrowing cause of drug-induced interstitial lung injury, with potentially higher incidence rates than conventional drugs, especially in lung cancer.
Keywords: adverse drug reactions; Fibrosis; Fibroza; intersticijska prizadetost pljuč; Intersticijske pljučne bolezni; interstitial lung injury; Lung Diseases, Interstitial; Lung Injury; medicines; neželeni učinki; Poškodba pljuč; zdravila